1998
DOI: 10.1056/nejm199811053391903
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Human Herpesvirus 8 Infection from Renal-Transplant Donors to Recipients

Abstract: HHV-8 is transmitted through renal allografts and is a risk factor for transplantation-associated Kaposi's sarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
157
0
4

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(168 citation statements)
references
References 18 publications
7
157
0
4
Order By: Relevance
“…In contrast, several studies of HHV-8 infection and KS have been reported after renal transplantation (10,11,16,22,27; Frances et al, letter). In two studies from different geographic areas (Switzerland and United States), HHV-8 seroprevalence increased from 5 to 6% before to 16 to 18% within the year after renal transplantation (22,27). Notably, KS is clearly more prevalent in the renal transplant population, approaching 4% of transplants (10,11), indicating that the pathogenesis of HHV-8 infection in the two transplant populations is different, which may be related in part to the shorter period of immunosuppression in SCT recipients.…”
Section: Vol 42 2004 Serological Methods For Detection Of Hhv-8 Antmentioning
confidence: 95%
See 3 more Smart Citations
“…In contrast, several studies of HHV-8 infection and KS have been reported after renal transplantation (10,11,16,22,27; Frances et al, letter). In two studies from different geographic areas (Switzerland and United States), HHV-8 seroprevalence increased from 5 to 6% before to 16 to 18% within the year after renal transplantation (22,27). Notably, KS is clearly more prevalent in the renal transplant population, approaching 4% of transplants (10,11), indicating that the pathogenesis of HHV-8 infection in the two transplant populations is different, which may be related in part to the shorter period of immunosuppression in SCT recipients.…”
Section: Vol 42 2004 Serological Methods For Detection Of Hhv-8 Antmentioning
confidence: 95%
“…Other studies have demonstrated that KS occurred rarely after bone marrow transplantation (21); only one case of KS, possibly transmitted by the donor, has been reported in a French cohort (20). In contrast, several studies of HHV-8 infection and KS have been reported after renal transplantation (10,11,16,22,27; Frances et al, letter). In two studies from different geographic areas (Switzerland and United States), HHV-8 seroprevalence increased from 5 to 6% before to 16 to 18% within the year after renal transplantation (22,27).…”
Section: Vol 42 2004 Serological Methods For Detection Of Hhv-8 Antmentioning
confidence: 96%
See 2 more Smart Citations
“…HHV-8 may be transmitted by blood transfusion or organ transplantation [17,18]. In high-prevalence countries, the seroprevalence increases during childhood, which suggests transmission between the mother and child, or sibling or playmate.…”
Section: Human Herpesvirus-8mentioning
confidence: 99%